2019
DOI: 10.1016/j.jtho.2019.03.028
|View full text |Cite
|
Sign up to set email alerts
|

Immune Cell Infiltration May Be a Key Determinant of Long-Term Survival in Small Cell Lung Cancer

Abstract: Introduction: Although most patients with SCLC die within a few months of diagnosis, a subgroup of patients survive for many years. Factors determining long-term survivorship remain largely unknown. We present the first comprehensive comparative genomic and tumor microenvironment analyses of SCLC between patients with long-term survivorship and patients with the expected survivorship.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
55
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(60 citation statements)
references
References 21 publications
5
55
0
Order By: Relevance
“…The exploration of the tumor microenvironment as a prognostic and diagnostic biomarker or therapy target is an area of active research [36]. Some studies have shown that immune cell infiltration has an influence on survival in lung cancer [37,38]. Other significant findings of the present study are that CLEC3B plays a role in tumor-immune interactions and that CLEC3B expression is correlated with the immune infiltration level in lung cancer, especially in SCC.…”
Section: Figsupporting
confidence: 54%
“…The exploration of the tumor microenvironment as a prognostic and diagnostic biomarker or therapy target is an area of active research [36]. Some studies have shown that immune cell infiltration has an influence on survival in lung cancer [37,38]. Other significant findings of the present study are that CLEC3B plays a role in tumor-immune interactions and that CLEC3B expression is correlated with the immune infiltration level in lung cancer, especially in SCC.…”
Section: Figsupporting
confidence: 54%
“…Nevertheless, the latest SCLC clinical studies showed no difference in intraepithelial CD3+ infiltration between patients with shorter vs. longer survival. However, significantly higher CD3+ infiltration in the stroma and at the cell-cell interface was present among patients with more prolonged survival (Muppa et al, 2019). Immune response evasion by tumors may play a crucial role in the aggressiveness of SCLC, and can be due to the insufficient number of T cells or T cells that are inhibited in the tumor microenvironment (Antonia et al, WCLC 2019).…”
Section: I and J)mentioning
confidence: 99%
“…Others showed that the extent of immunological infiltration in tumor tissue and the expression of immune checkpoints proved to be a reliable marker for response to anti-PD immunotherapy and long term survival in SCLC (Muppa et al, 2019;Bonanno et al, 2018); NSCLC , and other malignancies, like breast cancer (Bates et al, 2006), melanoma (Clemente et al, 1996), colorectal carcinoma (Galon et al, 2006), and prostatic cancer (Vesalainen et al, 1994) as well. Another group indicated on NSCLC TMA samples that a high number of stromal CD4+ and epithelial and stromal CD8+ cells were independent positive prognostic markers, and CD8+ Tumor-Infiltrating Lymphocytes (TILs) can stratify immunotherapy-treated patients of different clinical outcome (Lin Z et al, 2019).…”
mentioning
confidence: 99%
“…We have read with interest the article by Muppa et al 1 about the potential importance of immune cell infiltration for long-term survivorship (LTS) in patients with SCLC. Through comparing the differentially expressed genes between patients with LTS and patients with short-term survivorship, the authors found enriched numbers of tumor-infiltrating and associated lymphocytes in tumors in patients with LTS.…”
Section: To the Editormentioning
confidence: 99%
“…Recently, Boothman et al demonstrated that several clinical factors, such as the storage time of the paraffin specimen and prior chemoradiotherapy, result in significantly enhanced tumor expression of programmed death ligand 1. 2 The samples from patients with SCLC that were screened in the study by Muppa et al 1 were mainly taken from the archival formalin-fixed paraffin embedded surgical tissue specimens (sample age >3 months). The fresh biopsy specimens should be reanalyzed to provide a more accurate assessment of current immune cell profiling in individual SCLC tumors.…”
Section: To the Editormentioning
confidence: 99%